2014
DOI: 10.1007/s13197-014-1622-1
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of cobia (Rachycentron canadum) surimi: effect of washing cycle at different salt concentrations

Abstract: This study aimed to determine the effects of 2-5 wash cycles and the addition of tetrasodium pyrophosphate (TSPP) (0 %, 0.05 Surimi% and 0.1 % w/w)-with or without the addition of 0.4 % calcium chloride (CaCl2)-on the physical properties such as texture, colour, expressible moisture and microstructure of Cobia (Rachycentron canadum) surimi gel. The highest breaking force (484.85 g) was obtained with the addition 0.1 % TSPP alone on the fifth wash. However, a combination of 0.1 and 0.4 % CaCl2 in surimi gels at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
0
9
0
2
Order By: Relevance
“…39 Lower expressible moisture content of the gels suggests that more water was bound or retained in gel network. 40 Normally, gums or hydrocolloids have been used in restructured products for improving the water holding capacity. 37 The result suggested that GL could induce the formation of stronger network, in which more water could be held in the gel network.…”
Section: Resultsmentioning
confidence: 99%
“…39 Lower expressible moisture content of the gels suggests that more water was bound or retained in gel network. 40 Normally, gums or hydrocolloids have been used in restructured products for improving the water holding capacity. 37 The result suggested that GL could induce the formation of stronger network, in which more water could be held in the gel network.…”
Section: Resultsmentioning
confidence: 99%
“…However, the addition of higher concentration of chloride salts including calcium and magnesium chloride decreased the solubility of proteins (Petcharat & Benjakul, 2017). Meanwhile, another disadvantage of adding salt is that it reduces the flavor of the product by affecting the vapor pressure, thereby reducing flavor in the final product (Hamzah et al., 2015). Moreover, salt has been reported in several human health concerns, excessive intake of salt increases blood pressure, which is a major reason for cardiovascular diseases (Tahergorabi et al., 2012).…”
Section: Recent Developments In Cryoprotectantsmentioning
confidence: 99%
“…Expressible moisture of ultrasound-treated egg white gel for 40 minutes is the lowest (17.65%) as compared to other gels. Low expressible moisture content indicates that more water are retained in gel network due to the high water holding capacity (WHC) of gel (Hamzah et al, 2015). In the research of Huda et al (2013b), the amount of entrapped water in protein gel decreased as the expressible moisture increased.…”
Section: Expressible Moisturementioning
confidence: 99%